Integrating bioassays and analytical chemistry as an improved approach to support safety assessment of food contact materials. Issue 10 (3rd October 2017) - Veyrand, Julien; Marin-Kuan, Maricel; Bezencon, Claudine; Frank, Nancy; Guérin, Violaine; Koster, Sander; Latado, Hélia; Mollergues, Julie; Patin, Amaury; Piguet, Dominique; Serrant, Patrick; Varela, Jesus; et al.
ABSTRACT: Food contact materials (FCM) contain chemicals which can migrate into food and result in human exposure. Although it is mandatory to ensure that migration does not endanger human health, there is still no consensus on how to pragmatically assess the safety of FCM since traditional approaches would require extensive toxicological and analytical testing which are expensive and time consuming. Recently, the combination of bioassays, analytical chemistry and risk assessment has been promoted as a new paradigm to identify toxicologically relevant molecules and address safety issues. However, there has been debate on the actual value of bioassays in that framework. In the present work, a FCM anticipated to release the endocrine active chemical 4-nonyphenol (4NP) was used as a model. In a migration study, the leaching of 4NP was confirmed by LC-MS/MS and GC-MS. This was correlated with an increase in both estrogenic and anti-androgenic activities as measured with bioassays. A standard risk assessment indicated that according to the food intake scenario applied, the level of 4NP measured was lower, close or slightly above the acceptable daily intake. Altogether these results show that bioassays could reveal the presence of an endocrine active chemical in a real-case FCM migration study. The levels reported were relevant for safety assessment. In addition, this work also highlighted that bioactivity measured in migrate does not necessarily represent a safety issue. In conclusion, together with analytics, bioassays contribute to identify toxicologically relevant molecules leaching from FCM and enable improved safety assessment.